(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to find out about individual strategies for students with special needs during the pandemic. The subject of this research is an active teacher who teaches children with special needs. The research method used in this study is a qualitative method with interview analysis techniques via WhatsApp. This research is motivated by the pandemic phenomenon that has lasted for 2 years and has not ended, so teaching and learning activities are not conducive, especially for people with disabilities who need special strategies in learning, one of which is individual strategies. Therefore, researchers are interested in knowing more about how effective individual strategies for children with special needs are during the pandemic. The results showed that there were three sub-focuses: first, PPI planning for ABK, second, PPI implementation, and third, Evaluation. Individual strategies for children with special needs (ABK) are carried out with the support of the IEP (Individual Education Program). Individual strategies during the pandemic can be considered effective because, during class learning, children seem more focused (for some situations) because there are no distractions from friends around them.